Neuropathological Sequelae of Long-Term Allogeneic and Syngeneic Neural Transplantation into the Hippocampus - Patel, Sanjay N. (Hindawi Publishing Corporation, 1994)
The long-term fate of multiple intrahippocampal allogeneic transplants of fetal basal forebrain tissue was studied in neonatally tolerised and immunised groups of rats with lesions of the fimbria-fornix. Despite the good survival of the allografts in all groups, unexpected transplant-associated host hippo-campal neuropathology was discovered 12 months after transplantation, which consisted of (i) CA1 cell degeneration and (ii) abnormal accumulations of phosphorylated neurofilaments in neuronal perikarya and axonal swellings only within the host hippocampal neuropil and not of the transplanted tissue. This neurofilament abnormality, identified by RT97 immunohistochemistry, was significantly greater in the transplanted rats compared to the non-grafted lesion-only and sham-lesioned rats (p<0.01). The same type of neurofilament abnormality was again observed in a second, separate experiment using unilateral and bilateral syngeneic and allogeneic transplants. The neuropathology was significantly (p<0.05) greater in the transplanted side of the unilateral transplanted rats compared to the non-transplanted lesion-only control side of the same animals, showing that transplantation per se was a major factor involved in the pathogenesis of this neuropathology, irrespective of the type of transplant (syngeneic or allogeneic). In addition, a small degree of neurofilament abnormality was also found within the transplants in the second experiment, but not in the first. The results show that, under certain conditions, specific local neuropathological damage to the surrounding host neural tissue can develop in long-surviving allografted and syngrafted animals.